Factor XIII-A dynamics in acute myocardial infarction: a novel prognostic biomarker? - Gemmati, Donato; Zeri, Giulia; Orioli, Elisa; Mari, Rosella; Moratelli, Stefano; Vigliano, Marco; Marchesini, Jlenia; Grossi, Maria Elena; Pecoraro, Alessandro; Cuneo, Antonio; Ferrari, Roberto; Pinotti, Mirko; Serino, Luisa M.; Ansani, Lucia (Thrombosis and Haemostasis, 2015)
After acute myocardial infarction (MI) the damaged heart has to be repaired. Factor XIII (FXIII) is considered a key molecule in promoting heart healing. FXIII deficiency was associated to cardiac rupture and anomalous remodelling in MI. During MI, FXIII contributes firstly to the intracoronary thrombus formation and shortly after to heal the myocardial lesion. To quantify the real contribution of FXIII in this process, and to explore its possible prognostic role, we monitored the FXIII-A subunit levels in 350 acute MI patients during the first six days (d0-d5) plus a control at 30–60 days (d30). A one-year follow-up was performed for all the patients. A transient drop in the FXIII-A mean level was noted in the whole cohort of patients (FXIII-Ad0 99.48 ± 30.5 vs FXIII-Ad5 76.51 ± 27.02; p< 0.0001). Interestingly, those who developed post-MI heart failure showed the highest drop (FXIII-Ad5 52.1 ± 25.2) and they already presented with low levels at recruitment. Similarly, those who died showed the same FXIII-A dynamic (FXIII-Ad5 54.0 ± 22.5). Conversely, patients who remained free of major adverse cardiac events, had lower consuming (FXIII-Ad0 103.6 ± 29.1 vs FXIII-Ad5 84.4 ± 24.5; p< 0.0001). Interestingly, the FXIII-A drop was independent from the amount of injury assessed by TnT and CKMB levels. The survival analysis ascribed an increased probability of early death or heart failure inversely related to FXIII-A quartiles (FXIII-A25th< 59.5 %; hazard ratio 4.25; 2.2–5.1; p< 0.0001). Different FXIII-A dynamics and levels could be utilised as early prognostic indicators during acute MI, revealing the individual potential to heal and suggesting tailored treatments to avoid heart failure or its extreme consequence.Note: This paper was presented in part at the 14th Congress of the International Society on Thrombosis and Haemostasis, Amsterdam, Netherlands, June 29 – July 24, 2013.
Keywords: Factor XIII; myocardial infarction; myocardial healing; prognosis; myocardial infarction biomarkers